Costs, Staffing, and Services of Assisted Living in the United States: A Literature Review. Issue 2 (April 2016) - Kisling-Rundgren, Amy; Paul, David P.; Coustasse, Alberto
Abstract : Assisted-living facilities (ALFs), which provide a community for residents who require assistance throughout their day, are an important part of the long-term-care system in the United States. The costs of ALFs are paid either out of pocket, by Medicaid, or by long-term-care insurance. Monthly costs of ALFs have increased over the past 5 years on an average of 4.1%. The purpose of this research was to examine the future trends in ALFs in the United States to determine the impact of health care on costs. The methodology for this study was a literature review, and a total of 32 sources were referenced. Trends in monthly costs of ALFs have increased from 2004 to 2014. Within the past 5 years, there has been an increase on average of 4.1% in assisted-living costs. Medicaid is one payer for residents of ALFs, whereas another alternative is the use of long-term-care insurance. Unfortunately, Medicare does not pay for ALFs. Staffing concerns in ALFs are limited because of each state having different rules and regulations. Turnover and retention rates of nurses in ALFs are suggested to be high, whereas vacancy rate for nurses is suggested to be lower. The baby-boomer generation can be one contribution to the increase in costs. Over the years, there has been an increase in Alzheimer disease, which has had also an effect on cost in ALFs.